2021
DOI: 10.1142/s0129065721500076
|View full text |Cite
|
Sign up to set email alerts
|

Improving Botulinum Toxin Efficiency in Treating Post-Stroke Spasticity Using 3D Innervation Zone Imaging

Abstract: Spasticity is a common post-stroke syndrome that imposes significant adverse impacts on patients and caregivers. This study aims to improve the efficiency of botulinum toxin (BoNT) in managing spasticity, by utilizing a three-dimensional innervation zone imaging (3DIZI) technique based on high-density surface electromyography (HD-sEMG) recordings. Stroke subjects were randomly assigned to two groups: the control group ([Formula: see text]) which received standard ultrasound-guided injections, and the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Similarly, the non-reflex torque remains unchanged after the treatment [17]. Electrophysiological assessment has also been used to quantify the BoNT effects [31][32][33]. Zhang et al [33] measured compound muscle action potentials (CMAP) from the biceps muscles before, 3 wks and 3 mons after BoNT injections to the biceps muscles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the non-reflex torque remains unchanged after the treatment [17]. Electrophysiological assessment has also been used to quantify the BoNT effects [31][32][33]. Zhang et al [33] measured compound muscle action potentials (CMAP) from the biceps muscles before, 3 wks and 3 mons after BoNT injections to the biceps muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological assessment has also been used to quantify the BoNT effects [31][32][33]. Zhang et al [33] measured compound muscle action potentials (CMAP) from the biceps muscles before, 3 wks and 3 mons after BoNT injections to the biceps muscles. The authors reported both the MAS scores and CMAP values decreased at 3 wks and returned to baseline levels at 3 mons after the injections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, how IZ is distributed is an essential component for understanding muscle morphology and its alterations in diseased states [1][2][3][4][5]. In clinical practice, identification of muscle IZ can help facilitate botulinum toxin injection for spasticity treatment [6][7][8][9]. Knowledge of muscle IZ is also helpful for episiotomy during child delivery to minimize the risk of sphincter denervation [10].…”
Section: Introductionmentioning
confidence: 99%